An intelligent pH indicator film based on cassava starch/polyvinyl alcohol incorporating anthocyanin extracts for monitoring pork freshness. Issue 10 (8th August 2021) - Zhu, Bifen; Lu, Wangwei; Qin, Yuyue; Cheng, Guiguang; Yuan, Minglong; Li, Lin
Abstract: An intelligent pH indicator film was prepared by mixing cassava starch, polyvinyl alcohol (PVA), and natural anthocyanin extracted from grape skin (GSE) and mangosteen rind (MRE). The effects of GSE and MRE on the physical, structural, and pH‐sensing performance of composite films were studied. Scanning electron microscope results showed that the microstructure of film had little difference when the anthocyanin extracts were incorporated into the polymer matrix. A significant ( p  < .05) effect of GSE and MRE on the tensile strength, moisture content, and elongation at the break of the films were observed. The two indicator films could respond to different pH values and showed good color stability. During the storage of pork, the cassava starch/PVA/GSE film showed a visible color variation from pink, blue, purple to yellow, while the cassava starch/PVA/MRE film showed color variation from light yellow, bright yellow, green to dark green. The result indicated that the two films could be used to monitor pork freshness for intelligent pH indicator packaging. Novelty impact statement: Using fruit waste to extract anthocyanin. Indicator film has good color stability, and the color change was obvious at different pH values. The color of the indicator film changed obviously in the process of indicating the freshness of pork.